The Influence of Social Media Marketing, Product Variations, and Product Prices on Purchasing Decisions Using Buying Interest as an Intervening Variable in Bhinneka E-Commerce - Dyah Ayu Ramandani; Rauly Sijabat; Noni Setyorini (Value Management Research, 2025)
This research aims to determine the influence of social media marketing, product variety, and product price on purchasing decisions through purchasing interest in e-commerce diversity among Management study program students at PGRI University Semarang. Data was collected by filling out a questionnaire with a total of 99 respondents. Researchers used primary data obtained from distributing questionnaires via Google Form to students of the PGRI University Semarang study program. The technique used in sampling was non-probability sampling with a purposive sampling method. The respondents in this research were students of the Management study program at PGRI University Semarang. The results of this research identify that there is a correlation between social media marketing and price on buying interest in Bhinneka E-commerce, there is no correlation between product variety and buying interest in Bhinneka Ecommerce, that there is a correlation between social media marketing and purchasing decisions on Bhinneka E-commerce. -commerce Bhinneka, there is no correlation between product variables and purchasing decisions on E-commerce Bhinneka, that there is a correlation between buying interest and purchasing decisions on E-commerce Bhinneka, there is a correlation between social media marketing and price on purchasing decisions with buying interest as intervening variable in Bhinneka Ecommerce, there is no correlation between product variations on purchasing decisions and purchase interest as an intervening variable in Bhinneka E-commerce.